A nano-preparation approach to enable the delivery of daphnoretin to potentiate the therapeutical efficacy in hepatocellular cancer - Zhu, Guanglin; Wang, Bing; Feng, Guo; Zhou, Zhirong; Li, Wei; Liu, Wen; Su, Hongmei; Wang, Wenjing; Wang, Tiejie; Yu, Xie-an (Frontiers in Pharmacology, 2022)
Daphnoretin (DAP) isolated from a traditional Chinese medicine Wikstroemia indica (Linn. C. A. Meyer) could induce apoptosis of hepatocellular cancer (HCC) and inhibit tumor growth. However, the application of DAP in cancer therapies was hampered owing to its poor solubility and low bioavailability. Herein, this study aimed to design an approach of double-targeted nano-preparation enable delivery of DAP to potentiate the therapeutical efficacy in liver cancer via glycyrrhetinic acid-Polyethylene glycol-block-poly (D,L-lactic acid)/Polyethylene glycol-block-poly(D,L-lactic acid)-DAP (GPP/PP-DAP). In particular, DAP was obtain successively using the methods of percolation from Wikstroemia indica for extraction, column chromatography on silica gel for separation and methanol reflux for purification. GPP/PP-DAP was successfully prepared by thin film hydration method. Subsequently, the GPP/PP-DAP was optimized by the methods of single factor and response surface methodology, producing stable and systemically injectable nano-preparation, which exhibited sub-150-nm diameter and spherical structures. Impressively, on the one hand, cytotoxicity studies showed that the IC50 of the GPP/PP-DAP were lower than free DAP. On the other hand, the GPP/PP-DAP was more likely to be endocytosised by HepG2 cells and targeted to the liver of orthotopic mice, potentiating the therapeutical efficacy in HCC. Collectively, both in vitro and in vivo results indicated the excellent tumor inhibition and liver-targeting of GPP/PP-DAP, suggesting the nano-preparation could serve as a potential drug delivery system for natural products to lay the theoretical foundation for clinical application.